Pedro Opeka - Dober Prijatelj - Možina, Jože (Slovenia, 2011)
In 1989, Pedro Opeka came across a huge dump in Antananarivo, Madagascar, and discovered thousands of adults and children living there in appalling conditions. He was fundamentally shaken by this experience, and with incredible effort, he helped thousands of homeless to start new life. More than 23,000 of them now live in landscaped areas with new houses, schools, playgrounds and medical care.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films